Valery Gergiev and Leonidas Kavakos perform Prokofiev, Violin concerto no. 2 - Prokofiev, Sergey 1891-1953 (EuroArts Music International, 2013)
The violinist Leonidas Kavakos and the conductor Valery Gergiev perform Prokofiev's Violin Concerto No. 2 in G Minor, Op. 63. Composed in 1935, when Prokofiev was touring all over the world, the Violin Concerto No. 2 in G Minor, Op. 63 is assuredly one of the most popular concertos among violinists. The first movement, Allegro moderato, starts with a simple melody which reminds us of the Russian folk music. The melodic lines are fluid, the violin and the orchestra evolve together rather than against one another. The second movement, Andante assai, is graceful and lighthearted with the pizzicati accompaniment of the soloist by the orchestra. The third movement, in which castanets are added to the orchestra, draws freely its inspiration from Spanish music. Leonidas Kavakos, one of the most sought-after violinists on the international scene, is the soloist invited here to perform Prokofiev's Violin Concerto No. 2 in G Minor, Op. 63. He is accompanied by the Mariinsky Theatre Orchestra under Valery Gergiev's baton
Keywords: Concertos (Violon); Concertos (Violin); Webcast; Internet videos; Vidéos sur Internet